Ideational Dimensions of Wole Soyinka’s Idanre: Dramatic and Poetic Interpretations - Innocent Afolabi Ariremako; Bifatife Olufemi Adeseye (Britain International for Academic Research (BIAR-Publisher), 2022)
This paper examines the ideational dimension of Soyinka’s Idanre, in the light of two approaches. The first one is the Hallidayan approach which takes substance from Halliday’s Theories on group and phrase clauses under the classification of process, participant and circumstance. The second approach is the method adopted by the Indian linguist Syal, in his book entitled Structure and Stylein commonwealth Literature. This method is issued to analyze the ideational function of texts from the perspective of grammatical classes of words like verbs, nouns, adjectives, prepositional phrases etc. It derives the interpretation from the textuality of the text, taking into account the fact that textuality reflects a particular social and cultural orientation through meaning, stated or implied, embedded in the discourse. The purpose of this study is to see how the ideational functions have been used to allow entry into the world of Idanre and to have a fulfilling interpretation of the poem, using grammar as the basis for the analysis. The study shows that the use of the two approaches to the ideational dimension has the advantage of offering an in-depth interpretation of the poem.